EFEKTIVITAS TEPUNG BUNGA KECOMBRANG (Nicolaia speciosa Horan) SEBAGAI PRESERVATIF TERHADAP ASPEK MIKROBIOLOGIS DAGING BROILER - Gusti Putu Predika Wiguna; Rr. Riyanti; Purnama Edy Santosa (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
This study aims to: 1) determine the effect of kecombrang (Nicolaia speciosa Horan) flower powder on the microbiological aspects of broiler meat; 2) determine the optimum dose of kecombrang (Nicolaia speciosa Horan) flower powder as a preservative broiler meat. The method used completely randomized design (CRD), consisting of 4 treatments and 5 replications. Treatments are: P0: Carcasses with kecombrang flower powder dose 0%; P1: Carcasses with kecombrang flower powder doses 2%; P2: Carcasses with kecombrang flower powder dose 4%; P3: Carcasses with kecombrang flower powder dose 6%. Data were analyzed variance at 1%. If the results of the analysis show real results, then the test continued with Least Significant Difference (LSD) at 5%.The results showed that administration kecombrang flower powder was highly significant (P <0.01) to total plate count (TPC) and not significant (P> 0.01) on pH, Escherichia coli, and Salmonella. Dose 6% kecombrang flower powder could be used as broiler meat preservative. (Keywords: kecombrang (Nicolaia speciosa Horan) flower, broiler meat, microbiology, preservative)